EXPERIENCE WITH USING RAPID MOLECULAR TESTING IN DIAGNOSING PULMONARY AND EXTRA-PULMONARY PEDIATRIC TUBERCULOSIS IN A NON-ENDEMIC SETTING - A RETROSPECTIVE CASE SERIES. (18th May 2018) - Mijovic, Hana; Al-Nasser, Yossef; Al-Rawahi, Ghada; Roberts, Ashley
Abstract: BACKGROUND: Tuberculosis (TB) is a rare but potentially devastating infection among Canadian children. Accurate diagnosis and initiation of treatment are limited in part by the fact that it takes 2–6 weeks for culture results to be confirmed. Xpert MTB/RIF (Xpert) is a rapid, automated molecular assay that has been validated for diagnosing pulmonary but not extra-pulmonary TB in children. OBJECTIVES: This was a retrospective study of children investigated for active TB at our facility in order to: 1.Outline demographic characteristics and describe clinical presentations of children diagnosed with active TB. 2.Compare performance of molecular testing (Xpert) to stain and Mycobacterium tuberculosis culture on pulmonary and extra-pulmonary specimens. DESIGN/METHODS: We conducted a retrospective chart review of all paediatric patients investigated for active TB at our facility with stain, culture and molecular (Xpert) testing between January 2015 and August 2017. Due to a small number of patients, our data analysis was limited to narrative summary and descriptive statistics. RESULTS: A total of 10 children were diagnosed with active TB, including 3 cases of pulmonary, 4 extra-pulmonary and 3 disseminated disease. Age range at diagnosis was 2 months to 16 years, with 3 children younger than 1 year. Most children contracted TB while travelling to and/or being exposed to an index case from endemic areas, including East Asia/Western Pacific (5), South Asia (2) and Africa (1). All children were HIV negative. Time from symptom onset to TB diagnosis and treatment ranged from approximately 4 days to 5 months. Multi-drug resistant TB was confirmed in 1 child. Sadly, 1 child passed away from TB related complications. AFB stain was positive on at least one specimen in 4/10 cases, cultures were positive in 8/10 and molecular testing (Xpert) in 7/10 cases. Time to positive cultures ranged from 10 to 35 days, with an average of 19 days. All cases positive on Xpert were also culture positive. Xpert test diagnosed TB in 5/6 of extra-pulmonary specimens submitted, including pericardial fluid, lymph node tissues and cerebrospinal fluid. CONCLUSION: Many paediatric TB patients at our facility are children who have traveled to/have contacts from TB endemic regions, emphasizing the need for obtaining thorough exposure and travel history. Culture and molecular testing demonstrated similar TB detection rates, albeit based on a small patient population. While cultures remain the most reliable diagnostic method, molecular testing may facilitate rapid diagnosis and treatment of pulmonary and extra-pulmonary paediatric TB in a non-endemic setting.